Computational calculation of acetalization of 2-chlorobenzaldehyde reaction mechanism using hydrochloric acid catalyst with ab initio method - Muhammad Yusuf (Jurnal Pendidikan Kimia (JPKim), 2020)
The aim of this research was to investigate the possible reaction mechanism steps in the formation of acetal from 2-chlorobenzaldehyde substrate. Asetal is a chemical compound that attracts the attention of the researchers because it has advantage in various fields of life. This study was conducted using Hyperchem software (OS Window’s) with the ab initio method using a 6-31G* basis set. In this study, the 3-21G basis set was also used as a comparison. The calculations were performed for each steps of the reaction mechanism including the substrate, the formation of hemiacetal intermediate, and the formation of acetal products. Based on the results of computational calculations, the acetalization of 2-chlorobenzaldehyde reaction can occur in the presence of an HCl catalyst. The HCl catalyst serves as an acid catalyst where hydrogen ions will be protonated by the substrate and hemiacetal. Hemiacetal compounds based on calculations have the highest formation energy compared to the benzaldehyde substrate and acetal products. This is because hemiacetal has a low stability and is easily transformed into other compounds. Keywords: Ab initio; 2-chlorobenzaldehyde; acetal